Succulent plants nursery management system - Tey, Chee Leong (2022)

(untitled)
The project is planned to develop a mobile application for academic purpose. Report of project will include concept, research and design method of project. This will project aim to resolve problem of succulent gardener problem which in existing market and society. Therefore, the project aim to set scope and objective of develop system to resolve existing system problem and meet higher user requirement. By review existing system such as Plantnote, Plant Care Reminder and NatureID that available in google play store and identify the pro and cons of system to conclude a better system design by making comparison with existing system. Besides, design of system by waterfall model to develop system and follow the plan and procedure of system and identify the system requirement. The overall of project is planned to create a mobile-based application which overcome problem such as management of user plant list, unable to achieve of visualize sample of plants and poor instruction and guidance of gardening tips. To overcome the problem the project is aim to develop a system which able to achieve to resolve existing problem with innovative idea. The main function of this application will planned to develop system of create, read, update, delete of personalized plant list and get notify for task and date to watering, fertilize and repot the flower, get knowledge and caution by different type of plant. Another feature planned to develop it is community chat system which allow user to have discussion and chat in the post related to plants with friends and experts. The interesting part of application will planned to develop a mini game in the application.